Hipersuperfícies com curvatura média prescrita em variedades riemannianas - Alcantara, Priscila Rodrigues de (2010)
This work shows results existence and uniqueness of graphs with prescribed mean curvature. We demonstrate that a natural fixation Dirichlet problem for graphs of average curvature is required to consider those graphs like leaves on a Riemannian submersion Killing transversal cylinder, the cylinder given by flow lines of a Killing vector field. Using this approach, we are able to solve the problem in a way more comprehensive, giving a unified proof and existence results.